Power in Video Game Suikoden V: Its Relation and Exercises - Muhammad Fazar Izzamuddin Tengku; Ahmad Bukhori Muslim (Passage, 2020)
It has been a recent trend for video games to include story as part of the gameplay to further enhance the players experience in playing. However, as any other form in literature which may portray social issues within the story, games also have the same possibility to portray social issues, such as power. Because of this reason, the present study aims to investigate how power manifests among characters in a video game, Suikoden V. The study uses a qualitative method, and uses the theoretical framework from French and Raven (2008) to categorize the data acquired. Foucault’s (1982) theory of power is also used to analyze the findings. The present study finds that power is exercised frequently by the people of authority and in higher position such as nobles and leaders. Power often exercised for two major purposes. The first is for the leaders to control the people, and the second is to construct identities which allow the leaders to control the people more efficiently. The findings revealed how the leaders are able to construct the society through the use of various types of power.Keywords: characters, power, power relation, video games, French and Raven, Foucault.